2019
DOI: 10.3221/igf-esis.50.15
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the response to in-phase and out-of-phase multiaxial high-cycle fatigue loading

Abstract: This paper discusses the phase shift effect occurring between two and more load channels of multiaxially loaded specimens. The discussion concludes that there is an extreme shortage of good experimental data that would prove the existence and the trend of the phase shift effect in the highcycle fatigue region. It is no wonder that there are so many fatigue strength estimation criteria that use quite different computational concepts, because the response to the phase shift effect in the experimental base is oft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…A more practical comparison of the output of individual stress path description methods is thus desirable. Papuga et al designed in [ 13 ] a special sensitivity study, which allowed them to assess the response of various multiaxial fatigue strength criteria to the condition of a varying phase shift effect. Three different fictive materials were established to simulate a potentially different material response.…”
Section: Sensitivity Studymentioning
confidence: 99%
See 2 more Smart Citations
“…A more practical comparison of the output of individual stress path description methods is thus desirable. Papuga et al designed in [ 13 ] a special sensitivity study, which allowed them to assess the response of various multiaxial fatigue strength criteria to the condition of a varying phase shift effect. Three different fictive materials were established to simulate a potentially different material response.…”
Section: Sensitivity Studymentioning
confidence: 99%
“…The same procedure was also processed here. Whereas [ 13 ] focused solely on the MCC approach, here the MCE and MOI approaches were tested additionally. To check the typical response to various concepts of the multiaxial fatigue strength analysis, six different multiaxial criteria were chosen to compute the equivalent stress amplitude .…”
Section: Sensitivity Studymentioning
confidence: 99%
See 1 more Smart Citation
“…All analyses, results of which are described hereafter, were done with the analysis of the stress path parameters via the minimum circumscribed circle concept, as described by Papadopoulos et al in [ 25 ]. It is important to note that there are alternatives to this solution, as discussed by Meggiolaro et al [ 33 ] or by Papuga et al [ 34 ]—e.g., the minimum circumscribed ellipse method or the maximum prismatic hull. The difference in the method of processing the shear stress path would, however, concern only the two load cases of FF003 and FF004 run with the non-zero phase shift (see Table 4 ).…”
Section: Multiaxial Fatigue Strength Criteriamentioning
confidence: 99%
“…It proves statistically how simply the observation can lead to erroneous results if the testing matrix used for the proof is too small or if the number of interacting effects involved is too large. The recent research of Papuga et al 10 has revealed the considerable insufficiency of the existing experimental basis to prove whether the phase shift between tension and torsion load channels affects the fatigue life in high‐cycle fatigue and to what extent. The response to the phase shift effect is very important for a real variable amplitude loading.…”
Section: Introductionmentioning
confidence: 99%